'The necessity must be convincingly shown to exist': standards for compulsory treatment for mental disorder under the Mental Health Act 1983 - Bartlett, Peter (Oxford University Press, 2011)
Current English law has few controls on the involuntary treatment of persons detained under the Mental Health Act 1983. In 2001, R (Wilkinson)v. Broadmoor Special Hospital Authority provided some hope that, in conjunction with the Human Rights Act and the European Convention on Human Rights (ECHR), meaningful substantive and procedural standards for compulsory psychiatric treatment might be developed, but that hope has not been fulfilled. Using Wilkinson and the ECHR jurisprudence as a starting point, this article considers when, if at all, compulsory psychiatric treatment might be justified. In particular, it considers the difference between the ‘appropriateness’ standard of the English legislation and the ECHR requirement of ‘therapeutic necessity’, the requirements for appropriate procedure and appropriate legislative clarity, how the courts should deal with disagreements among treating physicians, and the relevance of the capacity and best interests of the detained person.